Creating effective abbreviations for brand names. - Tan, Sheila. (2008)
The purpose of this report is to explore three methods of creating effective abbreviated brand names and what properties should an effective abbreviated brand name have. The three methods are (1) truncation, (2) contraction and (3) including of vowels. Specifically, this report examines whether abstracting certain letters from the full brand or having an abbreviated brand name that contains a vowel affects consumers’ liking of that abbreviation. This report also studies the impact of having abbreviated brand names that are pronounceable and resemble English words on consumers’ familiarity towards and ease of recognition of the abbreviation, and ultimately consumers’ liking of the abbreviated brand name.